[6]-Shogaol Induces Ca2+ Signals by Activating the TRPV1 Channels in the Rat Insulinoma INS-1E Cells - Rebellato, Paola; Islam, Md. Shahidul (JOP. Journal of the Pancreas, 2014)
Context [6]-shogaol is a vanilloid compound present in steamed ginger (Zingiber officinale), a commonly used spice. Pancreatic beta-cells respond to nutrients like glucose, amino acids and fatty acids, by an increase in the cytoplasmic free Ca2+ concentration ([Ca2+]i), which mediates diverse cellular processes in these cells. Some vanilloid compounds activate the transient receptor potential vanilloid receptor type 1 (TRPV1) channel. Objective We investigated whether [6]-shogaol could trigger Ca2+ signals in the beta-cell. Methods [Ca2+]i was measured from single INS-1E cells by microscope-based fluorometry using fura-2 as the Ca2+ indicator. Results In fura-2 loaded single rat insulinoma INS-1E cells, a widely used model of beta-cell, [6]-shogaol increased [Ca2+]i in a concentration-dependent manner. [Ca2+]i increase by [6]-shogaol was completely blocked when Ca2+ was omitted from the extracellular medium. Capsazepine, an inhibitor of the TRPV1 ion channel completely inhibited the [6]-shogaol-induced [Ca2+]i increase. [Ca2+]i increase obtained by 1 µM [6]-shogaol was greater than that obtained by 10 mM glucose. Moreover, a sub-stimulatory concentration of [6]-shogaol (300 nM), significantly enhanced the glucose-induced [Ca2+]i increase in these cells. Conclusion We conclude that [6]-shogaol induces Ca2+ signals in the beta-cell by activating the TRPV1 channels, and it sensitizes the beta-cells to stimulation by glucose. Image: [6]-shogaol-induced [Ca2+]i increase.